The Effect of the Phospholipid Bilayer Environment on Cholesterol Crystal Polymorphism. Issue 4 (20th March 2019) - Varsano, Neta; Beghi, Fabio; Dadosh, Tali; Elad, Nadav; Pereiro, Eva; Haran, Gilad; Leiserowitz, Leslie; Addadi, Lia
Abstract: Invited for this month's cover are the group of Prof. Lia Addadi at the Weizmann Institute of Science, Israel and collaborators at the Università Degli Studi di Milano, Italy, and the ALBA Synchrotron Light Source, Spain. The front cover shows how cholesterol crystals form in macrophage cells and in lipid bilayers of different compositions. Cholesterol monohydrate stable triclinic crystals form in vitro as rhomb‐shaped plates, whereas the monoclinic crystals fold into tubular or helical shapes. Read the full text of the article at10.1002/cplu.201800632 . Abstract : "We suggest that rods and plates found in atherosclerotic plaques may indicate different lipid environments in which the crystals formed, and may thus provide information on their formation pathways in the pathological scenario." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201800632 ).